2021
DOI: 10.1098/rsif.2021.0555
|View full text |Cite
|
Sign up to set email alerts
|

Early warning signals of infectious disease transitions: a review

Abstract: Early warning signals (EWSs) are a group of statistical time-series signals which could be used to anticipate a critical transition before it is reached. EWSs are model-independent methods that have grown in popularity to support evidence of disease emergence and disease elimination. Theoretical work has demonstrated their capability of detecting disease transitions in simple epidemic models, where elimination is reached through vaccination, to more complex vector transmission, age-structured and metapopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 80 publications
(230 reference statements)
0
30
0
Order By: Relevance
“…In analyzing European data, some authors, e.g. Proverbio et al (2022) , resorted to the recent literature on early warning signals of disease re-emergence, EWS ( Southall et al, 2021 ) in order to better assess the beginning of a new wave, an important practical issue. For our analysis, we proceeded empirically, and considered the time interval from September 1st 2020 till January 31st 2021, a period when the second wave was surely under way.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In analyzing European data, some authors, e.g. Proverbio et al (2022) , resorted to the recent literature on early warning signals of disease re-emergence, EWS ( Southall et al, 2021 ) in order to better assess the beginning of a new wave, an important practical issue. For our analysis, we proceeded empirically, and considered the time interval from September 1st 2020 till January 31st 2021, a period when the second wave was surely under way.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…population collapse [33], recovery of a ecosystem [32] and the emergence of COVID-19 [34], although it has not been formally tested with a simulated control environment [35].…”
Section: Normalised Composite (2-sigma Threshold)mentioning
confidence: 99%
“…Here, a bootstrapping technique is proposed, which preserves the original features of the observed data and can be used to create the null distribution. However, the use of statistical tests and the misinterpretation of p-values have been previously criticised [4,38]; and other approaches have been proposed for estimating the null distribution.…”
Section: Changing P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…An approach derived from bifurcation theory on networks was applied on COVID-19 data in [ 19 ]. A review can be found in [ 20 ]. Performing more tests is thus a necessary next step towards the application of EWS in routine surveillance procedures.…”
Section: Introductionmentioning
confidence: 99%